EVALUASI PENERAPAN SISTEM AKUNTANSI PENGELUARAN KAS PENGGAJIAAN PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI UTARA - Roring, Pricilla Roxenne; Karamoy, Herman; Pangemanan, Sifrid (Universitas Sam Ratulangi, 2018)
The cash expenditure accounting system is an activity that the government cannot do without, the government reinforces caution in engaging in activities related to cash receipts and cash disbursements. The problem in this research is how the application of cash accounting system of Civil Employees at the Regional Civil Service Agency of North Sulawesi Province is implemented. The objective of this research is to evaluate the application of Cash Expenditure Accounting System, especially the payroll of civil employees. The type of this research is descriptive, using the qualitative method. Where an analysis collects, organizes, and manages, in order to provide a picture of a particular situation so that it can be deduced. The results of this study indicates that the payroll cash expenditure accounting system of civil employees at the Regional Civil Service Agency of the North Sulawesi Province has been applied well in accordance with the qualitative characteristics of the financial reports as it can be proven with existing data. In conclusion regarding the Cash Expenditure Accounting System at the Regional Civil Service Agency of North Sulawesi Province is in accordance with government regulation No.13 since 2006.Keywords : Accounting system, cash expenditure, evaluation